Attachment anxiety and smartphone addiction among university students during confinement: Teacher–student relationships, student–student relationships and school connectedness as mediators - Zhang, Wen; Zhou, Fangzhou; Zhang, Qingyu; Lyu, Zhixuan (Frontiers in Public Health, 2022)
Learning at home during the COVID-19 confinement might affect students’ relationships with their peers, teachers, and schools and increase the possibility of smartphone addiction. We hypothesized that attachment anxiety directly and indirectly affects smartphone addiction, with teacher–student relationships, student–student relationships, and school connectedness as mediators. The participants were 999 university students from different regions of China. The results showed that six of the paths were significant except the one between student–student relationships and smartphone addiction. Also, the association between attachment anxiety and smartphone addiction was mediated by teacher–student relationships and school connectedness not but student–student relationships. The current study highlights the mediating effect of school connectedness and teacher–student relationships in the multiple mediation model, and suggests that universities can alleviate the risk of smartphone addiction in distance teaching by cultivating good teacher–student relationships and strengthening students’ sense of belonging to their schools.